Scaled Quail Habitats Revisited - Oklahoma Panhandle - Sanford D. Schemnitz (National Quail Symposium Proceedings, 2017)
Scaled quail (Callipepla squamata) populations declined 50% from 1954-56 to 1990–91 in a 125 km2 study area. Food habits based on a sample of 150 quail crops remained unchanged. Abandonment of farms, land use, and climatic changes were hypothesized to be major factors responsible for the population decline.
Keywords: Callipepla squamala; food habits; habitat; population; scaled quail